Assessment of outcomes based on the use of PIM-supported foresight modeling work, 2012-2018 - Lowder, Sarah K.; Regmi, Anita (International Food Policy Research Institute, 2019)
This report presents results of a study to assess the use of foresight modeling tools and outputs produced since 2012 and funded through Flagship 1, Cluster 1.1 of the CGIAR Research Program on Policies, Institutions, and Markets (PIM). The goal of this study is to examine how the tools and outputs of foresight modeling supported by PIM through Flagship 1 (hereafter “PIM-supported foresight modeling”) have been used by stakeholders. The study aims to identify as many uses of and outcomes from the PIM-supported foresight modeling as possible. It is by no means comprehensive, but it does cover usage by a wide range of stakeholders from across the CGIAR system, other international organizations, academia, and national governments.